PROSPECTIVE OBSERVATIONAL STUDY ON ANTIBIOTIC-PRESCRIBING PATTERN AND MEDICATION ERRORS IN SURGICAL PROPHYLAXIS IN A SPECIALTY HOSPITAL - KUMAR N, SENTHIL; K, SIVASAKTHI; JOSEPH, JISA ELIZABETH; VA, VISHNUKUMAR; RP, GEOLIN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective was to study the antibiotic-prescribing patterns, identify the medication errors and impact of surgical antimicrobial prophylaxis (SAP) in preventing surgical site infection (SSI), and to understand the prescribers’ adherence to surgical prophylaxis guidelines. Methods: The study was conducted for a period of 6 months in all surgical departments of a specialty hospital. Data were collected from inpatients records. Australian guideline for SAP was used to assess the appropriateness in prescribing pattern. The sample size was calculated using Raosoft sample size calculator. Results: A prospective observational study was carried out among 178 patients. Of which, 100 were male and 78 were female. Four hundred and thirty-three antimicrobials were prescribed as pre- and post-operative surgical prophylaxis, among that 87% prescribed by brand name and 13% by generic. Seventy-one percent received single antimicrobial agent preoperatively, of which 99.5% prescribed as parenteral and 0.5% as oral formulation. Most often prescribed antibiotic was cefoperazone (28%) of cephalosporin group. Only 5.6% of cases had compliance with SAP guidelines. In this study, 11 patients affected with SSI due to inappropriate antibiotic selection and non-adherence to prophylactic antibiotic guidelines. Conclusion: The present study revealed that there is a poor compliance to SAP guidelines in terms of inappropriateness in antibiotic drug selection, dose, duration, and omission of drugs. Inappropriateness and non-compliance are mainly due to unavailability of clinical pharmacist to assist the physicians in the selection and administration of correct choice of prophylactic drug and unavailability of proper national or local guidelines. Hence, there is dire need to make local SAP guidelines to improve SAP-prescribing pattern.